EFFECT OF REDW STRATEGY WITH PEER SUPPORT ON STUDENTS’ READING COMPREHENSION ACHIEVEMENT - Ade Suhendri (Universitas Muhammadiyah Metro, 2022)
The research aimed to investigate the effect of the REDW (Read, Examine, Decide, Write) Strategy with peer support on students’ reading comprehension achievement and their responses towards implementing the strategy. This research employed a quantitative method with a quasi-experimental one-group pretest and posttest design. The population was all the second-year students of MAS Al-Manar Modern Islamic Boarding School. The sample chosen was class A which consisted of 30 students. Test and questionnaires were used as instruments to collect data. The data were analyzed using SPSS 21 version (Cohen, 2013). The findings indicated that the REDW Strategy with peer support has a significant effect on students’ achievement in reading comprehension. The posttest average score is 23 points higher than the pretest score and the Cohen's d value, which is 1,948 greater than 0.8. Furthermore, the students responded positively to implementing the strategy which they mostly agreed with the questionnaire statements. In conclusion, the REDW strategy with peer support significantly affects students' achievement in reading comprehension and gaining positive responses. Therefore, it is suggested that the REDW strategy with peer support should be implemented in teaching reading comprehension.